2017
DOI: 10.1021/acsami.6b14223
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Film Nanocomposite (TFN) Membranes Incorporated with Super-Hydrophilic Metal–Organic Framework (MOF) UiO-66: Toward Enhancement of Water Flux and Salt Rejection

Abstract: Zirconiumv (IV)-carboxylate metal-organic framework (MOF) UiO-66 nanoparticles were successfully synthesized and incorporated in the polyamide (PA) selective layer to fabricate novel thin-film nanocomposite (TFN) membranes. Compared to unmodified pure polyamide thin-film composite (TFC) membranes, the incorporation of UiO-66 nanoparticles significantly changes the membrane morphology and chemistry, leading to an improvement of intrinsic separation properties due to the molecular sieving and superhydrophilic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
141
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(151 citation statements)
references
References 67 publications
9
141
1
Order By: Relevance
“…Findings showed that the water flux increased by 44% comparing to the plain membrane by adding 0.05% MIL-101 NPs to the organic solution, while the salt rejection remained almost the same. Similar outcomes were observed by Ma et al [58] when embedding UiO-66 in membranes used in forward osmosis. By loading 0.1% NPs to the membrane, the water flux increased from 2.19 to 3.33 LMH/bar.…”
Section: Introductionsupporting
confidence: 86%
“…Findings showed that the water flux increased by 44% comparing to the plain membrane by adding 0.05% MIL-101 NPs to the organic solution, while the salt rejection remained almost the same. Similar outcomes were observed by Ma et al [58] when embedding UiO-66 in membranes used in forward osmosis. By loading 0.1% NPs to the membrane, the water flux increased from 2.19 to 3.33 LMH/bar.…”
Section: Introductionsupporting
confidence: 86%
“…As a prototype Zr-MOF, UiO-66 has displayed interesting physical and chemical characteristics for the preparation of highly water-stable MOF membranes for liquid separation. [22][23][24] The highly regular structure of UiO-66 with the aperture size of about 6.0 A, 25,26 which is located between H 2 O (2.6 A) and hydrated ions (e.g. Na + 7.2 A, Mg 2+ 8.6 A, SO 4 2À 7.6 A, Cl À 6.6 A), is promising for achieving high ux and sustains high salt rejections by ionic sieving.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic approaches for composites of MOFs and scaffolds mainly include: (1) directly fill MOFs particles in matrices and the composite membranes are fabricated by solution casting approach. While this extensively applied method has two main problem: one crucial issue is the inevitable agglomeration of MOFs particles and the other is the adhesion of MOFs on matrices needs to be enhanced; (2) tether polymer monomers onto MOFs particles, and utilize the copolymerization process to integrate both together; (3) in situ growth on scaffolds via solvothermal growth in precursor or microwave irradiation, whichever is chosen, it can avoid the agglomeration of MOFs particles and ensure the strong link between MOFs and scaffolds . Thus integrating MOFs with membrane materials via in situ growth seems to be a more promising strategy.…”
Section: Introductionmentioning
confidence: 99%